ATP-Binding Pocket-Targeted Suppression of Src and Syk by Luteolin Contributes to Its Anti-Inflammatory Action - Jeong-Oog Lee; Deok Jeong; Mi-Yeon Kim; Jae Youl Cho (Mediators of Inflammation)
Luteolin is a flavonoid identified as a major anti-inflammatory component of Artemisia asiatica. Numerous reports have demonstrated the ability of luteolin to suppress inflammation in a variety of inflammatory conditions. However, its exact anti-inflammatory mechanism has not been fully elucidated. In the present study, the anti-inflammatory mode of action in activated macrophages of luteolin from Artemisia asiatica was examined by employing immunoblotting analysis, a luciferase reporter gene assay, enzyme assays, and an overexpression strategy. Luteolin dose-dependently inhibited the secretion of nitric oxide (NO) and prostaglandin E2 (PGE2) and diminished the levels of mRNA transcripts of inducible NO synthase (iNOS), tumor necrosis factor- (TNF-) α, and cyclooxygenase-2 (COX-2) in lipopolysaccharide- (LPS-) and pam3CSK-treated macrophage-like RAW264.7 cells without displaying cytotoxicity. Luteolin displayed potent NO-inhibitory activity and also suppressed the nuclear translocation of NF-κB (p65 and p50) via blockade of Src and Syk, but not other mitogen-activated kinases. Overexpression of wild type Src and point mutants thereof, and molecular modelling studies, suggest that the ATP-binding pocket may be the luteolin-binding site in Src. These results strongly suggest that luteolin may exert its anti-inflammatory action by suppressing the NF-κB signaling cascade via blockade of ATP binding in Src and Syk.